2023
DOI: 10.3390/ma16103706
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Oyster Shell Powder on the High-Temperature-Properties of Slag-Ceramic Powder-Based Geopolymer

Abstract: There is a lack of scientific understanding of adding an oyster shell powder (OSP) to geopolymer concrete. The purpose of this study is: (1) to evaluate the high-temperature resistance of the alkali-activated slag ceramic powder (CP) mixture added with OSP at different temperatures, (2) to address the lack of application of environmentally friendly building materials, and (3) to reduce solid waste of OSP pollution and protect the environment. OSP replaces granulated blast furnace slag (GBFS) and CP at 10% and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Other researchers have investigated the properties of base-activated materials. Zhang et al [ 11 ] studied the high-temperature resistance of a slag ceramic powder base polymer added with oyster powder. Their research found that adding oyster shell powder to the sample can effectively reduce the high-temperature damage (800 °C) to the alkali-activated material.…”
mentioning
confidence: 99%
“…Other researchers have investigated the properties of base-activated materials. Zhang et al [ 11 ] studied the high-temperature resistance of a slag ceramic powder base polymer added with oyster powder. Their research found that adding oyster shell powder to the sample can effectively reduce the high-temperature damage (800 °C) to the alkali-activated material.…”
mentioning
confidence: 99%